Reading the Bible Positively Popular Reading of the Bible with people living with HIV/AIDS in Brazil - Schroder, Elisa Fenner (Missionalia: Southern African Journal of Missiology, 2015)
In the early 60s, it began to emerge, in Latin America and Brazil, political movements that sought to raise awareness about their situation of oppression and theneed for ruptures with the dominant society. The Bible had been given to the people and was read from the experience and reality of men and women in situations ofoppression. The situations of oppression and exclusion experienced in Latin America broaden the understanding about the poor and the excluded and challenges newreadings of the Bible from each context. Prejudice and stigma affects the lives of people with HIV, causing them suffering. The situation of social vulnerability affecting a major portion of this population complicates the lives of these people even further. We seek to read the Bible through the context of lives of women with HIV by using popular bible reading methodology. This article bring some introductions reflection on the method and on the experience of a women group in Brazil.